Fusion of protegrin-1 and plectasin to MAP30 shows significant inhibition activity against dengue virus replication. - Hussin A Rothan; Hirbod Bahrani; Zulqarnain Mohamed; Noorsaadah Abd Rahman; Rohana Yusof (PLoS ONE, 2014)
Dengue virus (DENV) broadly disseminates in tropical and sub-tropical countries and there are no vaccine or anti-dengue drugs available. DENV outbreaks cause serious economic burden due to infection complications that requires special medical care and hospitalization. This study presents a new strategy for inexpensive production of anti-DENV peptide-fusion protein to prevent and/or treat DENV infection. Antiviral cationic peptides protegrin-1 (PG1) and plectasin (PLSN) were fused with MAP30 protein to produce recombinant antiviral peptide-fusion protein (PG1-MAP30-PLSN) as inclusion bodies in E. coli. High yield production of PG1-MAP30-PLSN protein was achieved by solubilization of inclusion bodies in alkaline buffer followed by the application of appropriate refolding techniques. Antiviral PG1-MAP30-PLSN protein considerably inhibited DENV protease (NS2B-NS3pro) with half-maximal inhibitory concentration (IC50) 0.5±0.1 μM. The real-time proliferation assay (RTCA) and the end-point proliferation assay (MTT assay) showed that the maximal-nontoxic dose of the peptide-fusion protein against Vero cells is approximately 0.67±0.2 μM. The cell-based assays showed considerable inhibition of the peptide-fusion protein against binding and proliferating stages of DENV2 into the target cells. The peptide-fusion protein protected DENV2-challeged mice with 100% of survival at the dose of 50 mg/kg. In conclusion, producing recombinant antiviral peptide-fusion protein by combining short antiviral peptide with a central protein owning similar activity could be useful to minimize the overall cost of short peptide production and take advantage of its synergistic antiviral activities.